Deep subwavelength split ring neck acoustic resonator - Ming Yuan; Fan Yang; Zongqiang Pang (Results in Physics, 2019)
Here, a novel acoustic resonator is proposed, realizing deep sub-wavelength form. An embedded split ring neck configuration is adopted, which makes the acoustic resonator being flat while lowering the acoustic resonance frequency. This resonant frequency can also be varied through changing the length of split ring neck. The effectiveness of analytical prediction is demonstrated through a case study, and perfect sound absorption is realized in low frequency range. The thickness of the proposed acoustic resonator is 1/79 of the resonant frequency’s wavelength, making such apparatus deep subwavelength. Keywords: Acoustic resonator, Low frequency, Deep subwavelength, Perfect sound absorption